Karakteristik Media Video Pembelajaran Desain Kostum - Anita Volintia Dewi; Afif Ghurub Bestari; Kapti Asiatun; Sri Widarwati; Sugiyem Sugiyem (Journal on Education, 2023)
Learning video media has an important role to contain information or instructional messages and can be used in the learning process. In addition, video media can also increase the enthusiasm and enthusiasm of students in participating in the learning process. Costume Design competency learning in the Fashion Design Education Study Program still uses the lecture method and direct demonstrations, so video media is needed to help students explore creativity. Research on the characteristics of Costume Design Learning Video media uses the R&D approach 4 development models of Alessi & Trollip (2001), consisting of 3 stages. namely planning, design, and development. Based on the results of the research and discussion, it can be concluded that the development of the characteristics of the learning video for the Costume Design course goes through 3 stages. The planning stage is to ensure that everything is needed in the project, including: defining the breadth of coverage, identifying students, developing boundaries, producing planning documents, producing manuals, determining and gathering resources, conducting brainstorming, and seeking student approval. Design includes developing ideas, conducting task and concept analysis, preparing prototypes, creating flowcharts and story boards, preparing scripts, downloading Ibis Paint supporting software. The development stage includes: preparing text, preparing graphics, producing audio and video, assembling materials using supporting software.